2020
DOI: 10.1002/jmv.25884
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 3062 COVID‐19 patients: A meta‐analysis

Abstract: Objective:We aim to systematically review the clinical characteristics of Coronavirus disease 2019 .Methods: Seven datebases were searched to collect studies about the clinical characteristics of COVID-19 from 1 January 2020 to 28 February 2020. Then, meta-analysis was performed by using Stata12.0 software. Results:A total of 38 studies involving 3 062 COVID-19 patients were included.Meta-analysis showed that a higher proportion of infected patients were male (56.9%).The incidence rate of respiratory failure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
530
15
33

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(658 citation statements)
references
References 28 publications
43
530
15
33
Order By: Relevance
“…Gastrointestinal symptoms were also present with diarrhoea being the most common one. As compared to the other studies (33,34,37,43,44), fever and cough had similar WPP, however, dyspnoea was found to be more prevalent in older patients as compared to the younger ones. Similarly, though diarrhoea has been noted as the most common gastrointestinal symptom in other studies (33,43) too, it has comparatively higher WPP in older population.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Gastrointestinal symptoms were also present with diarrhoea being the most common one. As compared to the other studies (33,34,37,43,44), fever and cough had similar WPP, however, dyspnoea was found to be more prevalent in older patients as compared to the younger ones. Similarly, though diarrhoea has been noted as the most common gastrointestinal symptom in other studies (33,43) too, it has comparatively higher WPP in older population.…”
Section: Discussioncontrasting
confidence: 38%
“…A marginal difference was observed when the subgroup analysis was done for patients in China (15%) and outside China (11%), which was not statistically signi cant. The published meta-analysis on COVID-19 has reported its mortality ranging from 3.1-5.5% (32)(33)(34)37). Hence, the fatality rate in our study is signi cantly higher, re ecting the poor resilience of older patients to COVID-19.…”
Section: Discussionmentioning
confidence: 51%
“…Common laboratory findings include lymphocytopenia and increased values of C-reactive protein (CRP), lactate dehydrogenase (LDH), D-dimer, and erythrocyte sedimentation rate (ESR). On chest X-ray or chest computed tomography, bilateral lung involvement was common [32,37]. Diagnosis of SARS-CoV-2 is currently performed with reverse transcription polymerase chain reaction (PCR-RT) testing for nucleic acid sequence homology in nasopharyngeal or throat swabs [38].…”
Section: Covid Pandemicmentioning
confidence: 99%
“…Common clinical COVID-19 manifestations include fever, cough, fatigue, expectoration, shortness of breath, dyspnoea, and muscle soreness 11 . The median incubation period is estimated to be 5.1 days (95% CI, 4.5 to 5.8 days), and 97.5% of those who develop symptoms will do so within 11.5 days (95% CI, 8.2 to 15.6 days) of infection 12 .…”
Section: Introductionmentioning
confidence: 99%